Implementasi Aliran Filsafat Perenialisme dalam Pengembangan Pendidikan Islam - Muhammad Taqiyuddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article is organized with the determination to investigate and describe how the idea of perennialism, the formative history and character of perennialism and its implementation in Islamic education. The exploration technique in this article is a subjective examination strategy. It is a kind of library examination, and the investigation of the information involves inquiry. The result is that the idea of perennialism suggests a message about the presence of perennial status in values and standards. Perennialism is definitely not another school of thought. Perennialism in schools was persuaded by the philosophical ideas of Aristotle, Plato, Thomas Aquinas at the time. The figures of perennialism are: Seyyed Hossein Nasr and Frithjof Schuon, the two figures above are figures that will generally last. With respect to its implementation in the realm of Islamic education, it can be found in the objectives of Islamic teaching, the duties of instructors and members of instruction, Islamic school education plans, learning techniques and assessments.